Prediktor Kinerja Usaha UMKM Kedai Kopi - Djaya, Adythia; Ida Puspitowati (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to analyze the influence of entrepreneurial orientation and social media adoption on the performance of coffee shop MSMEs in West Jakarta with innovation capability as a moderating variable. The research method uses a quantitative approach with a purposive sampling technique, data were collected through distributing questionnaires to 78 coffee shop MSMEs. Data analysis was carried out using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS 4 software. The results showed that entrepreneurial orientation has a positive and significant effect on social media adoption and business performance. In addition, social media adoption has also been shown to have a positive effect on business performance and acts as a mediator in the influence of entrepreneurial orientation on business performance. Innovation capability is known to have a positive influence on business performance and is able to strengthen the influence of social media adoption on business performance. It is concluded that improving the performance of coffee shop MSMEs can be achieved through strengthening entrepreneurial orientation, optimizing the use of social media, and developing innovation capabilities on an ongoing basis. Keywords: Business Performance, Entrepreneurial Orientation, Innovation Capability, Social Media Adoption.